The Future of Historical European Martial Arts Studies - Daniel Jaquet (Acta Periodica Duellatorum, 2016)
The two panels of the conference were concluded by a round-table aiming at discussing the future of HEMA studies, by crossing the views of the speakers on three levels: personal involvement, major contribution needed for the field, strategies to make it happen. This article will focus on (1) reviewing the most important matters discussed and to balance them with the latest published desiderata for further research, (2) situating them in the latest developments in, on the one hand, martial arts studies, and on the other, Practice as Research (PaR) in other fields of research, and finally (3) comparing them with the developments of a similar fields of study over the last 60 years, notably dance studies.